The handbook of convertible bonds : pricing, strategies and risk management - Spiegeleer, Jan de.; Schoutens, Wim. (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2011)
This is acomprehensive guide to the pricing and risk management of this hihgly profitable asset class in a post credit crunch setting. it introduces the convertibles market, covering the impact that the 2008 credit crunch has had on the markets.
Includes bibliographical references (p. ([363]-368) and index.
uaj 29/04/13
Loans
Keywords: Convertible bonds -- Handbooks, manuals, etc